India and Europe/Germany. Spatial Structures and Trends. - Kundu, Debolina; Müller, André; Binot, Regine; Ghatak, Aparajita; Kiel, Lukas; Mondal, Biswajit; Pandey, Arvind; Schmidt-Weiwert, Volker (My University, 2019)
Today, 55 % of the worldwide population lives in urbanized areas according to the Revised 2018 UN Urbanization Prospects. These prospects estimate that the percentage of the global urban population will increase to 68 % by 2050. Against this background, the percentage of the urban population would rise in the EU from 76 % as of today to 85 %, whereas in Germany the percentage would rise from 77 % to 84 % in 2050 and in India from 35 % to 53 % (United Nations 2018). Urbanization is thus both, an international and national phenomenon. In response to the ongoing urbanization, the General Assembly of the United Nations adopted the New Urban Agenda. Urban issues also constitute an integral part of its 2030 Agenda and the 17 Sustainable Development Goals. Against the background of urbanization, the Federal Government of Germany has agreed upon bilateral urbanization partnerships - in this case with India. Urbanization processes may best be understood by the respective role of cities, the systems of cities, the expansion of cities and the urban sprawl, particularly in selected urban areas, as well as migration and remittance flows. This volume reacts on the urbanization reality and contributes to the ongoing dialogue by illustrating spatial structures and trends in India and Europe/Germany. It thus focuses on jointly harmonised and visualised data in order to deliver compatible and comparable spatial pictures based on a common data-oriented language.
Keywords: Siedlungsstruktur; Siedlungsdichte; Bevölkerungsdichte; Verstädterung; Urbanisierung; Stadtwachstum; Verdichtungsraum; Wanderungsbewegung; Internationaler Vergleich